2017
DOI: 10.29321/maj.2017.000088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Indeterminate Tomato (Solanumlycopersicum L.) Genotypes for Growth and Yield Traits under Polyhouse Condition

Abstract: A study was conducted during the period of June 2015 to January 2017 at college orchard of Tamil Nadu Agricultural University, Coimbatore with an objective to evaluate tomato (Solanum lycopersicum L.) genotypes suitable for polyhouse condition. Fifty one genotypes received from diverse agro climatic regions were used for evaluation of twenty characters in a randomized block design with two replications. The genotypes were assessed for plant height, days to first flowering, number of flowers per truss, number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…According to Premalakshmi et al, (2017), plant height is an important trait by which growth and vigour of the plants were measured. In cluster bean, fruit length is one of the desirable characters for vegetable purpose.…”
Section: Growth and Yield Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Premalakshmi et al, (2017), plant height is an important trait by which growth and vigour of the plants were measured. In cluster bean, fruit length is one of the desirable characters for vegetable purpose.…”
Section: Growth and Yield Parametersmentioning
confidence: 99%
“…Lokesha and Shivsankara (1990) reported that pod weight strongly associated with fruit length, fruit weight and total yield. Fruit yield is determined by the fruit weight and number of fruits per plant therefore yield is complex character and dependent on its component traits and their inheritance any change in these would reflect on total yield (Premalakshmi et al, 2017).…”
Section: Growth and Yield Parametersmentioning
confidence: 99%